2014
DOI: 10.3109/0886022x.2014.976130
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid may predict development of progressive acute kidney injury after open heart surgery

Abstract: Objectives: Acute kidney injury (AKI) is a common complication of cardiac surgery developing in 25-35% cases. Recently, neutrophil gelatinase-associated lipocalin (NGAL) was shown to predict AKI development earlier than serum creatinine. Some studies demonstrated the predictive role of post-operative serum uric acid (SUA) as an early marker of AKI. We aimed to study the role of serum and urine NGAL as well as SUA to predict progression of AKI. Design and methods: This is a prospective observational study of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Recently our group reported that even modest hyperuricemia increases the risk for AKI following aortic aneurysm repair or cardiovascular surgery [38], [39]. In one study, hyperuricemia (preoperative serum uric acid >7 mg/dL) was found to confer a 35-fold increased risk for AKI that was independent of other risk factors including a baseline reduction in eGFR [40].…”
Section: Uric Acid In Acute Kidney Injurymentioning
confidence: 99%
“…Recently our group reported that even modest hyperuricemia increases the risk for AKI following aortic aneurysm repair or cardiovascular surgery [38], [39]. In one study, hyperuricemia (preoperative serum uric acid >7 mg/dL) was found to confer a 35-fold increased risk for AKI that was independent of other risk factors including a baseline reduction in eGFR [40].…”
Section: Uric Acid In Acute Kidney Injurymentioning
confidence: 99%
“…Serum uric acid (SUA) is an independent risk factor for acute kidney injury (AKI) in cardiac surgery patients [1,2,3,4,5]. SUA is also an independent predictor of tumor lysis syndrome (TLS) in acute myeloid leukemia (AML) patients and has comparable discriminative performance with traditional and cytogenetic-based prediction models of TLS [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently Kim JH et al investigated association between uric acid level and mortality and AKI after paraquat intoxication and found significantly higher level of UA in AKI and death groups 8 . Gaipov A et al also reported higher prediction capability of AKI at 24 and 48 hrs with UA and with NGAL, in open heart surgery patients 9 . Apart from an early marker of AKI, UA is now also becoming a potential therapeutic target in kidney diseases 10,11 .…”
Section: Resultsmentioning
confidence: 91%